Pengaruh Kesejahteraan dan Motivasi Kerja Terhadap Kepuasan Kerja Guru di Ma’had Al Izzah Leadership School Malang - Qonitah Cahyaning Tyas; Jazirotunnada; Fathalloh (PT. ALHAFI BERKAH INDONESIA, 2023)
The teacher is the component that most influence the creation of quality educational processes and outcomes. For this reason, efforts to develop, coach, and train teachers are also needed, but this also requires each teacher's contribution to support this development activity to create better-quality schools as a teacher or teacher educator is one of the determining factors for the success of any educational effort. To improve good teacher performance, factors in it in the form of teacher welfare, work motivation, and job satisfaction. Therefore, the researcher chose the Al-Izzah Leadership School Islamic Boarding School as the research location. This study aims to determine the effect of teacher welfare and work motivation on teacher job satisfaction. This study used quantitative research. In this study, the population was Al-Izzah Islamic Boarding School Teachers, and the sample was 50 teachers at Al-Izzah Islamic Boarding School. Collecting data in this study using questionnaires and data analysis techniques using ordinal logistic regression analysis. The results of this study indicate that teacher welfare and work motivation affect job satisfaction by 62%, which means that other factors influence 38%. Teacher welfare has a significant positive effect on job satisfaction, while work motivation has no significant impact.